Ma’na Al-Sadaqah Fi Al-Qur’an (Dirasah Dalaliyyah Qur’aniyyah) - Muhammad Badrun; Raka Fadel Devarsa Pahlawan (Universitas Darussalam Gontor, 2020)
It is believed that “ Al-Shadaqah” is giving partially of the wealth to the poor. Al-Asfahani argued that “Al-Shadaqah” is a bride price to the woman. Prophet Muhammad SAW stated that every kindness is Shadaqah. This study aimed to reveal the meaning of Shadaqah based on the word derivation and context which include on semantic studies to disclose the secret meaning and the wisdom in language. It was found that there were five meaning of Shadaqah. In context, shadaqah means in all its forms, zakat, acceptance of repentance, apology and bride price of woman. In term of derivation, it was found that Al Shadaqah has some form of sentences. Here are singular form (Shadaqotun) , Plural form (Shadaqaat), Verb form ( Tashaddaqa ), Present form ( Ashaddaqa), imperative form ( Tashaddaquu) and Noun ( Mutashaddiqun)